Pengaruh Peran Kepala Unit dan Beban Kerja terhadap Budaya Keselamatan Pasien Melalui Implementasi Handover Perawat-Farmasi - Aini Nadhifah; Rokiah Kusumapradja; Nofierni Nofierni (Syntax Corporation Indonesia, 2022)
The application of patient safety culture is one of the hospital's efforts in keeping patients from experiencing unexpected events. This study uses a quantitative approach with a causal design research design using a variant-based VB-SEM, PLS (Partial Least Square), aimed at analyzing influences that can improve the cultural values of patient safety in hospitals. The study used a saturated sample of 77 people (room nurse staff and pharmacy). The results of this study showed that there was a positive influence on the role of the head of the unit on the culture of patient safety, the negative influence of workload on patient safety culture, the positive influence of the implementation of nurse-pharmacy handovers on patient safety culture, the positive influence of the role of the head of the unit on the implementation of nurse-pharmacy handovers.positive influence of the role of the head of the unit on the patient safety culture through the implementation of nurse-pharmacy handover as an intervening variable, where the results of tstatistic>ttabel and probability (pvalue) measurements 0,000<0.05, and there is no negative influence of workload on the implementation of nurse-pharmacy handovers, and there is no negative influence of workload on patient safety culture through the implementation of nurse-pharmacy handovers as intervening variables where results are tstatistics<ttabel and probability (pvalue) >0.05. Based on the results of the study, the implications in this study show the influence of the role of the head of the unit on the culture of patient safety through the implementation of handovers as planners, organizing, military, directing and supervision in the implementation of effective and efficient handovers to improve patient safety in hospitals